The Role of Organizational Support in Work Engagement Among Nurses Working in Intensive Care Units - Marwa Badwan; Nidal Eshah; Rayan Ahmad (Journal of Holistic Nursing and Midwifery)
Introduction: The challenges and difficulties of working in intensive care units put pressure on healthcare professionals, especially nurses. To support nurses working in intensive care units (ICUs), developing supportive climates in organizations may drive nurses towards increasing work engagement levels and other related factors. Objective: This study aimed to determine the relationship between organizational support and the work engagement of nurses working in ICUs. Materials and Methods: This correlational cross-sectional study was conducted on 140 nurses working in two governmental hospitals in Amman City, Jordan, from January to August 2021. The participants were selected with a simple random sampling method, and study data were collected using a 3-part questionnaire: demographics, the survey of perceived organizational support scale with 8 items, and the Utrecht work engagement scale with 9 items. Descriptive statistics, the independent t test, the Spearman correlation test, and hierarchal multiple linear regression analysis were performed to determine the contribution of perceived organizational support on nurses' work engagement. The significance level for all tests was set to be less than 0.05. Results: About 53.6% of participants were male, 55% worked in medical-surgical intensive care units, and 45% were in cardiac care units. The results showed that the mean ± SD scores of perceived organizational support and work engagement were 29.53 ± 6.71 and 3.71 ± 0.88, respectively. Also, results showed no significant differences in perceived organizational support and work engagement based on nurses' socio-demographics or work-related factors. Finally, there was a significant positive weak correlation between perceived organizational support and work engagement (r= 0.23, P=0.002). The linear regression model showed that perceived organizational support could predict work engagement (R2 = 0.039). Conclusions: Perceived organizational support among nurses working in ICUs is one of the important factors in increasing work engagement. Findings have several implications for nurses in different settings. Jordanian health policymakers must take action to improve nurses' perception of organizational support and consequently increase nurses' work engagement.